Seasonal Study of Aflatoxin M1 Contamination in Cow Milk on the Retail Dairy Market in Gorgan, Iran - Hadi Rahimzadeh Barzoki; Hossein Faraji; Somayeh Beirami; Fatemeh Zahra Keramati; Gulzar Ahmad Nayik; Zahra Izadi Yazdanaabadi; Amir Sasan Mozaffari Nejad (Dairy, 2023)
Milk and milk products are the main nutritional foods for all age groups, especially for infants and children. Milk may be dangerous to consume due to the presence of a harmful substance called Aflatoxin M1 (AFM1). The objective of this study was to assess the levels of AFM1 in milk, particularly those that exceed the standards set by the European Union (50 ng/L), the Food and Drug Administration (500 ng/L), and the Iranian National Standards Organization (100 ng/L). The study included one hundred and eighty samples of raw cow’s milk from various retail dairy markets in Gorgan, with 45 samples collected during each season. The level of Aflatoxin M1 in the samples was measured using the enzyme-linked immunosorbent assay (ELISA) technique. AFM1 was detected in 139 (72.2%) raw cow milk samples with a range of 3.5–357 ng/L. All of the samples collected had Aflatoxin M1 concentration levels that were below the maximum limit of 500 ng/L set by the FDA. However, 41 samples (22.7%) exceeded the EU’s limit of 50 ng/L, and 26 samples (14.4%) exceeded the INSO’s limit of 100 ng/L for Aflatoxin M1 in raw cow’s milk. The lowest and highest AFM1 levels of contamination were detected in the summer and winter seasons, which constituted 32 (71.1%) and 38 (84.4%) samples, respectively. The consumption of raw cow milk can lead to health risks for individuals from various age groups because regulatory limits are not being followed.